Educação especial na perspectiva da educação inclusiva: em foco a formação continuada de professores em São Luís-MA - BORGES, Tamires Coimbra Bastos (2024)
This research's main objective is to analyze how the training of teachers for special education has been taking place from the perspective of inclusive education in regular elementary schools in the public education network in São Luís-MA. Its theoretical contribution is, among others, Caiado (2003), Carvalho; Moraes (2015), Costa (2013), Duarte (2010), Kassar (2014), Martins (2010), Saviani (1998). This is qualitative bibliographical, documentary and field research (MYNAIO, 1994) whose method is historical-dialectical materialism (MARX; ENGELS, 1998; KOSIK, 1969), especially with regard to the categories historicity, praxis, totality and contradiction. Mixed questionnaires were used as data collection instruments. The research participants constituted two groups: regular education teachers and Specialized Educational Service teachers. The data was organized, coded, categorized and analyzed using content analysis as proposed by Bardin (2011). The results demonstrate that teachers' perceptions are convergent with the hypotheses of this research: the understanding that teachers develop in relation to the school inclusion of the target student of special education presents itself positively towards inclusion, although the feeling of insecurity, doubt and pessimism regarding inclusion is present in the speech of these teachers. Furthermore, the following hypothesis was also confirmed: teachers do not feel prepared to work with target students of special education in regular education classrooms, as they do not consider that their training is sufficient or adequate to carry out inclusion. of special education target audience students in their classrooms. The hypothesis was also found that teachers evaluate the teacher training and special education policy from the perspective of inclusive education carried out in the public education network in São Luís as insufficient or inadequate to meet the demands for teacher qualifications. To this end, he defends the thesis that public school education is everyone's right and the continued training of teachers is one of the fundamental elements for the effectiveness of inclusive education in regular education classrooms, therefore teacher training must go beyond the content merely technical and practical and promote spaces for collective reflection for the construction of theoretical knowledge that enables the development of critical teaching action.